ICESag37, a Novel Integrative and Conjugative Element Carrying Antimicrobial Resistance Genes and Potential Virulence Factors in Streptococcus agalactiae - Zhou, Kaixin; Xie, Lianyan; Han, Lizhong; Guo, Xiaokui; Wang, Yong; Sun, Jingyong (Frontiers in Microbiology, 2017)
ICESag37, a novel integrative and conjugative element carrying multidrug resistance and potential virulence factors, was characterized in a clinical isolate of Streptococcus agalactiae. Two clinical strains of S. agalactiae, Sag37 and Sag158, were isolated from blood samples of new-borns with bacteremia. Sag37 was highly resistant to erythromycin and tetracycline, and susceptible to levofloxacin and penicillin, while Sag158 was resistant to tetracycline and levofloxacin, and susceptible to erythromycin. Transfer experiments were performed and selection was carried out with suitable antibiotic concentrations. Through mating experiments, the erythromycin resistance gene was found to be transferable from Sag37 to Sag158. SmaI-PFGE revealed a new SmaI fragment, confirming the transfer of the fragment containing the erythromycin resistance gene. Whole genome sequencing and sequence analysis revealed a mobile element, ICESag37, which was characterized using several molecular methods and in silico analyses. ICESag37 was excised to generate a covalent circular intermediate, which was transferable to S. agalactiae. Inverse PCR was performed to detect the circular form. A serine family integrase mediated its chromosomal integration into rumA, which is a known hotspot for the integration of streptococcal ICEs. The integration site was confirmed using PCR. ICESag37 carried genes for resistance to multiple antibiotics, including erythromycin [erm(B)], tetracycline [tet(O)], and aminoglycosides [aadE, aphA, and ant(6)]. Potential virulence factors, including a two-component signal transduction system (nisK/nisR), were also observed in ICESag37. S1-PFGE analysis ruled out the existence of plasmids. ICESag37 is the first ICESa2603 family-like element identified in S. agalactiae carrying both resistance and potential virulence determinants. It might act as a vehicle for the dissemination of multidrug resistance and pathogenicity among S. agalactiae.